THE ROLE OF GENE MODIFIERS ON CLINICAL COURSE OF DUCHENNE MUSCULAR DYSTROPHY - Kosac, Ana (Medicinski podmladak, 2023)
ABSTRACT Duchenne muscular dystrophy is the most common inherited muscle disease in childhood, which has a progressive clinical course with a fatal outcome that most often occurs between second and fourth decade of life. The disease is inherited X-linked, recessively, and in two thirds of patients it is transmitted from the mother, while in the remaining third of patients it is a "de novo" mutation. Mutations in the dystrophin gene (DMD gene) such as deletions, duplications and small mutations can be found throughout the entire length of the gene. The disease begins between the third and fifth year of life, and the initial muscle weaknesses are clinically manifested as slower running, difficulty climbing stairs or difficulty getting up from squats. Sometimes, accidentally discovered, elevated keratin kinase values ​​or delayed early psychomotor development milestones in a child with hypertrophic calves can initiate a diagnostic procedure in the direction of Duchenne muscular dystrophy. The disease usually has a uniform clinical course and implies a clear time sequence of events. Muscle weakness leads to loss of ambulation, then the function of the upper extremities, to complete immobility, with the evolution of dilated cardiomyopathy and respiratory insufficiency, which are the main cause of death. Certain patients show deviations from the above in terms of longer functionality and later loss of independent ambulation, later cardiomyopathy and respiratory insufficiency and vice versa. It is believed that in addition to the application of modern standards of care and treatment of patients, the clinical course is influenced by genes independent of the causal DMD gene, which affects processes in dystrophic muscle, primarily inflammation, fibrosis and fatty infiltration, through specific signaling pathways. So far, six genes have been described whose variants modify the course of Duchenne muscular dystrophy. SPP1 (secreted phosphoprotein 1) is the first described gene whose G allele in the variant rs28357094 is associated with an earlier age of gait loss. In addition, variants in the genes described are: LTBP4 (latent transforming growth factor-β binding protein 4), CD40, ACTN3 (actinin 3), THBS1 (thrombospondin 1) and TCTEX1D1 (Tctex1 domain containing 1). The aim of this paper is to present till now known genes that modify Duchenne muscular dystrophy and their influence on the clinical course of the disease.